Indirect Contributions of Neocolonial Era on Urdu Language - Attaullah, Muhammad; Ovaisi, Muhammad Arshad; Arshad, Waseem (sourcecoder, 2023)
Cultural relations are established under the colonial system. In this system the colonizer gets monopoly at every level. Therefore, the above mentioned cultural relations are actually power relations. The metaphorist is in a position to create and enforce most forms of power (eg: political, academic, economic, educational, and artistic). They were popularized through educational and literary associations and books. This is the reason that nationalism, protest, resistance and dual personality attitudes in Urdu literature were the response to these narratives. While writing the history of Urdu language, the question often comes up as to what role the colonial rulers played in the promotion and development of Urdu language. What did there is no doubt that the influence of English language on Urdu is very deep and far-reaching.